Characteristics of unemployment dynamics: The chain reaction approach - Marika Karanassou; Dennis J. Snower (Institute for Advanced Studies (IHS), 2007)
The aim of this paper is to analyze and estimate salient characteristics of unemployment dynamics. Movements in unemployment are viewed as "chain reactions" of responses to labour market shocks, working their way through systems of interacting lagged adjustment processes. In the context of estimated labour market systems for Germany, the UK, and the US, we construct aggregate measures of unemployment responses to temporary and permanent shocks. These measures are temporal and quantitative. Furthermore, we estimate the contributions of individual lagged adjustments to these aggregate measures. Our empirical results indicate that lagged adjustment processes play an important part in explaining how temporary and permanent shocks affect unemployment, that temporary and permanent shocks can yield quite different inter-country comparisons of unemployment effects, and that the quantitative and temporal measures can also yield markedly different inter-country comparisons.
Keywords: E30; J64; J60; E37; J32; 330; Unemployment; Natural rate hypothesis; Labour markets; Employment; Adjustment costs; Arbeitslosigkeit; Hysteresis; Schock; Arbeitsmarkt; Wirtschaftliche Anpassung; Anpassungskosten; Schätzung; Vergleich; Deutschland; Großbritannien; USA